Characteristic Evaluation of Wind Power Distributed Generation Sizing in Distribution System - Issarachai Ngamroo; Wikorn Kotesakha; Suntiti Yoomak; Atthapol Ngaopitakkul (Sustainability, 2023)
Energy consumption and environmental issues have become major drivers of increasing renewable energy penetration levels. The electricity generated from renewable energy sources is decentralized throughout distributed generation (DG), which is located at the distribution level. However, the presence of DG can change distribution system characteristics and affect protection systems. Thus, this study aims to investigate the impact of DG in term of its sizing and placement on distribution systems under both normal and fault conditions. In addition, the effects on voltage improvement under normal conditions and current under fault conditions are also considered. The case study system in this study was modelled after an actual section of a 22 kV distribution line from the Provincial Electricity Authority of Thailand using PSCAD software. For DG, wind turbine generation was selected as a renewable energy source. The simulation results demonstrated that the presence of DG has a significant impact on both voltage and current characteristics under both normal and fault conditions. These impacts on the distribution system caused by DG can affect the operation of conventional distribution systems, which require further analysis and preventive measures in order to ensure good system reliability.
Keywords: Islanding Detection in Power Systems; Power Systems Fault Detection; Optimal Power Flow Distribution